Structural Performance of Cold Form Steel Truss and its Comparison with Hot Rolled Steel - Salve, Sachin; Shinde, Sunil (AMC Indian Journal of Civil Engineering, 2020)
This paper presents analytical observation results on the performance of cold formed steel truss and hot rolled steel truss. Two trusses of same dimensions and same type with different materials have been studied and compared. Both the materials are compared on the basis of fast, better, and economic construction. One truss is completely designed and analyzed in hot rolled steel while the same model is designed in cold formed steel. Both the trusses are designed in ETABS. Results of the present study would be handy in designing a truss that leads to optimal use of material. In constructions of residential and industrial buildings, the use of cold-formed steel (CFS) structures has now grown-up considerably, and now it is becoming a suitable alternative to general and conventional methods due to its massive advantages, like it is very light weight, it has high quality, and ease of construction. The present research targets to evaluate the lateral performance of cold formed steel truss systems. This research is crucial for improving the design of cold-formed steel (CFS) truss structures because there is unavailability of adequate information presently in the available codes and standards.